PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN AFTER SALES TERHADAP MINAT BELI ULANG (REPURCHASE INTENTION) PADA PT. NORD DRIVESYSTEMS INDONESIA TANGERANG SELATAN - Tino, Tino; Fadillah Fadillah (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to determine the effect of Product Quality, Brand Image, and After-Sales Service on Repurchase Intention among customers of PT NORD Drivesystems Indonesia. This research employed a quantitative method. The sampling technique used was simple random sampling with a total sample of 85 customers of PT NORD Drivesystems Indonesia. Data analysis techniques included validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient analysis, coefficient of determination, and hypothesis testing. The results show that Product Quality has a significant effect on Repurchase Intention with a coefficient of determination of 22.5%, and the hypothesis test indicates that t-count > t-table (4.234 > 1.989). Brand Image also has a significant effect on Repurchase Intention with a coefficient of determination of 45.9%, and the hypothesis test shows that t-count > t-table (5.172 > 1.989). After-Sales Service has a significant effect on Repurchase Intention with a coefficient of determination of 42.8%, and the hypothesis test shows that t-count > t-table (4.924 > 1.989). Simultaneously, Product Quality, Brand Image, and After-Sales Service have a significant effect on Repurchase Intention, as indicated by the regression equation Y = 11.107 + 0.008X₁ + 0.394X₂ + 0.343X₃. The coefficient of determination is 52.9%, while the remaining 47.1% is influenced by other factors. The hypothesis test shows that F-count > F-table (30.326 > 2.720).